Mencari Akar Rumput Kejahatan Begal oleh Pelaku Muda dalam Upaya Perlindungan Hukum dan Rasa Aman Masyarakat Kota Jambi - S. Sahabuddin; Warfian Saputra; Syarifa Mahila (Wajah Hukum, 2022)
The begal crime  has recently been very troubling for the people of Jambi City. This crime was committed by a group of motorcycle gangs against road users by seizing the victim's property, even injuring the victim's body. Even more surprising, this robbery crime was committed by young perpetrators whose average age was between 14 to 16 years. This is an interesting social phenomenon to examine the most basic factors that cause these young perpetrators to commit robbery crimes and at the same time find the most appropriate solution to anticipate it. This research was funded by Batanghari University in an effort to serve the community.